Generation and Validation of Crack Growth Resistance Curve from DCB Specimens: An Experimental Study - Alfred Franklin, V.; Christopher, T. (Проблемы прочности, 2013)
This article examines fracture toughness and
interlaminar failure load of double cantilever
beam (DCB) specimens made of glass/epoxy of
three different lay-ups. The present model requires
the applied load–displacement history
and crack extension to generate the crack
growth resistance curve (R-curve). From the generated
R-curve, the interface failure load was estimated
for the specimens and good agreement
with the experimentally recorded value was
found. Исследуются вязкость разрушения и межслойная разрушающая нагрузка для образцов в виде
двухконсольной балки из стекла/эпоксидной смолы, которые наносились тремя разными
слоями. Для построения кривой трещиностойкости (R-кривая) с помощью представленной
модели необходимо знать историю приложенной нагрузки–перемещения и распространение
трещины. На основе построенной R-кривой определена разрушающая нагрузка на границе
раздела слоев для образцов. Полученное значение разрушающей нагрузки хорошо соответствует экспериментальному значению. Досліджується в’язкість руйнування і міжшарове руйнівне навантаження для
зразків у вигляді двоконсольної балки зі скла/епоксидної смоли, що наносились трьома різними шарами. Для побудови кривої тріщиностійкості (R-крива) за допомогою представленої моделі необхідно знати історію прикладеного навантаження – переміщення та розповсюдження тріщини. На основі
побудованої R-кривої визначено руйнівне навантаження на границі поділу
шарів для зразків. Отримане значення руйнівного навантаження добре збігається з експериментальним.